Overview of Meningitis: Causes, Symptoms, Treatment, and Differential Diagnosis - Targoński, Oskar; Targońska, Marta; Niekurzak, Rafał; Madej, Adrianna; Suława, Adrian; Buczek, Agnieszka; Basiak, Aneta; Ptasiński, Aleksander; Furgalska, Julia; Fedorowicz, Sebastian (Quality in Sport, 2024)
Introduction and purpose: Meningitis is a serious condition that requires quick diagnosis and rapid implementation of appropriate treatment. Every primary care physician should be particularly alert to symptoms that may suggest meningitis as the cause of a patient's complaints. The purpose of this article is to present the most common causes of meningitis, symptoms to which special attention should be paid during diagnosis, and the treatment used. State of knowledge: Meningitis is an inflammatory process resulting from the penetration of microorganisms into the cerebrospinal fluid - it can be caused by viruses, less commonly by bacteria, fungi, and parasites. Infections usually occur as a result of generalized infections through the transfer of pathogens via the bloodstream, although infections spreading through tissue continuity also occur. Summary: Meningitis is an inflammatory process resulting from the penetration of microorganisms into the cerebrospinal fluid - it can be caused by viruses, less commonly by bacteria, fungi, and parasites. Characteristic symptoms suggesting infection of the meninges can aid in diagnosis. Recognition of this clinical condition is a key element of diagnostics, as it requires absolute hospitalization, determination of the cause, and implementation of intensive treatment, as untreated meningitis can be associated with high mortality.